Concurrent Exertional Compartment Syndrome and Functional Popliteal Artery Entrapment Syndrome: A Case Report. Issue 6 (28th March 2019) - Drigny, Joffrey; Reboursière, Emmanuel; Desvergée, Antoine; Ruet, Alexis; Hulet, Christophe
Abstract : Exertional leg pain is a common and disabling condition in athletes with challenging diagnosis and management. We report the case of a 29‐year‐old rugby player with a history and clinical examination consistent with chronic exertional compartment syndrome (CECS). Compartment pressure measurement was supportive of the diagnosis. However, magnetic resonance angiography (MRA) with provocative maneuvers showed functional popliteal artery entrapment syndrome (PAES). For the treatment of CECS, bilateral fasciotomy of the anterolateral compartments permitted return to full sport participation in 8 weeks. A follow‐up MR angiogram at 12 months showed resolution of the popliteal entrapment leading us to hypothesize a possible relationship between CECS and functional PAES.